Prioritizing agricultural research for development : experiences and lessons (CABI, 2009)
This book shows how a diversity of methods have been used to fit specific CGIAR Centre contexts (whether global and regional, or research-focused on genetic improvement or natural resources management), with more emphasis on simpler and more transparent methods that are readily understandable to a broader set of participants. Increasingly too, repeated priority assessment exercises in individual centers and integration of ex ante and ex post impact assessment have enabled learning and feedback to be built into the process. The book consists of 13 chapters presented in four parts: background tools, institute level approaches, system and regional approaches and synthesis and options for enhanced priority assessment for agricultural and natural resources research.